Should Gottfried Ostermeyer be Considered an Amateur Historian? - Barasa, Darius (Senoji Lietuvos literatūra, 2016)
The paper focuses on historical studies by Gottfried Ostermeyer (1716–1800) with the aim of assessing the extent of amateurishness and scholarship in his historical works. The emergence of history as a field of study and as a separate discipline and of the issue of whether the scholars into the past of the Epoch of Enlightenment can be seen as professional historians are also addressed. The author attempts to assess Ostermeyer’s works against the general background of the studies into the past in Prussia during the particular period and to determine how his works were engaged in the academic circulation by scholars of later times and to what extent his works are relevant to present-day researchers. Before the early nineteenth century, history had not been formed as a field of study and as an academic discipline. It means that professional history researchers and scholars were not trained. The past used to be investigated by persons who had studied theology, law, or Classical languages, thus, formally, none of the prominent history researchers, even if they had written outstanding historical works by the end of the eighteenth century, could be referred to as professional historians. To a certain extent, they all can be seen as amateurs, some of them more scholarly than others. Ostermeyer described himself as an amateur historian, which shows he did not consider himself an academic history scholar: to him, studies into the past were just one of favourite intellectual activities. His opponents, who disagreed with conclusions of his research, called him an amateur as well. From the point of view of scholarship, Ostermeyer’s works received mixed opinions. Historical papers published in continuous publications resemble texts of local lore studies that fulfil hardly any criteria of an academic work. However, a researcher of quite a different calibre figures in the works that were published as separate books: Kritischer Beytrag zur Altpreußischen Religionsgeschichte (A Critical History of the Old Prussian Religion; Marienwerder, 1775), Gedanken von den alten Bewohnern des Landes Preußen (Thoughts on the Old Inhabitants of the Prussian Land; Königsberg und Leipzig, 1780), and Erste Littauische Liedergeschichte (The First History of Lithuanian Hymns; Königsberg, 1793). They highlight Ostermeyer’s critical approach to sources, his mistrust in the arguments of authoritative authors, the claims to revise them, and the like. Clearly defined research objectives, a consistent presentation and structure of the work, well-founded and justified arguments create the impression of scholarliness. On the other hand, in some instances the amount of historiographical and primary sources is too scarce, the restraint necessary for academic works is quite often not maintained and from time to time the emotional polemic style and phrases inconsistent with the academic style burst out; also, a fair amount of methodological blunders is observed. In general, Ostermeyer’s works contain considerable elements of the academic approach, which are, nonetheless, outbalanced by qualities characteristic of an amateur researcher, or a dilettante. Ostermeyer successfully engages linguistic elements, in particular etymology, in his historical studies, but then he starts to depend on them too much and to explain many historical aspects exclusively through etymology. The portrait of Ostermeyer as a researcher is of many layers: he is a historian, a linguist, and a theologian. Quite often a tangible rivalry between Ostermeyer-historian and Ostermeyer-linguist is felt. It is this factor that makes one raise the question whether Ostermeyer can in general be treated as a historian alone, without associations with the linguist. It would probably be most accurate to describe him as a cultural historian who was ahead of his time and who displayed prominent qualities of an interdisciplinary researcher.